Religious Groups and Their Influence on Interstate Relations (The Case of U.S.-Israel Relations) - I. Istomin (Vestnik MGIMO-Universiteta)
The impact of interest groups on foreign policy of the state up until today has not received substantial attention in the theory of international relations. In particular, activities of the entities shaped by the common religious affiliation of their members lack assessment in the academic literature. Meanwhile, their mobilization in the recent decades became significant aspect of political life both in developing and developed countries. The activity of religious groups in the United States forced deep transformation of the national political landscape, as they desire to affect not only internal debate, but external policies as well. Among other issues attention of such social and political bodies is also focused on the situation in the middle East. Their proactive standing facilitated advancement of the partnership between the United States and Israel, including growth of American diplomatic and military aid to Tel-Aviv. The supporters of such policy include not only small, but well organized Jewish community, but also representatives of the conservative Evangelical Protestants, which constitute the most numerous religious group in the U.S. Despite the fact that leaders of both group often use theological reasons to justify their support for Israel, the real motivation of the most regular members is primarily humanitarian and pragmatic. The diversity of the Pro-Israeli groups promotes bipartisan support of cooperation between the two countries, and enabled creation of both Democratic and Republican lobby on this issue. However the growing criticism of the current policy of Tel-Aviv on behalf of some of the adherents of American-Israeli cooperation leads to the erosion of impact of these groups.